2021
DOI: 10.1186/s40733-021-00081-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nebulized ketamine and intravenous magnesium sulfate on corticosteroid resistant asthma exacerbation; a randomized clinical trial

Abstract: Background and aims Asthma exacerbation is defined as an acute attack of shortness of breath with more than 25% decrease in morning peak flow compared to the baseline on 2 consecutive days, which requires immediate standard therapy. The majority of asthmatic patients are considered to be steroid-sensitive; however, corticosteroid-resistant asthma is a subset of asthma with poor response to corticosteroids and is responsible for frequent hospital admissions. In this study we aimed to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…44 Ketamine has been investigated as a potential treatment for acute asthma attack and refractory status asthmaticus in part due to its sympathomimetic hemodynamic effects, analgesic and sedative effects, and bronchodilating properties. Ketamine has been shown to reduce the likelihood of intubation in children and adults suffering from acute asthma attacks 26,27,29,45 as well as alleviate lung injury by decreasing pro-inflammatory cytokines. [46][47][48][49] In addition to intravenous, inhalational administration of ketamine was shown to improve the peak expiratory flow rates (PEFR) in patients with acute severe asthma that had not responded well to traditional treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Ketamine has been investigated as a potential treatment for acute asthma attack and refractory status asthmaticus in part due to its sympathomimetic hemodynamic effects, analgesic and sedative effects, and bronchodilating properties. Ketamine has been shown to reduce the likelihood of intubation in children and adults suffering from acute asthma attacks 26,27,29,45 as well as alleviate lung injury by decreasing pro-inflammatory cytokines. [46][47][48][49] In addition to intravenous, inhalational administration of ketamine was shown to improve the peak expiratory flow rates (PEFR) in patients with acute severe asthma that had not responded well to traditional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] In addition to intravenous, inhalational administration of ketamine was shown to improve the peak expiratory flow rates (PEFR) in patients with acute severe asthma that had not responded well to traditional treatments. 27 Interestingly, some researchers have reported that children receiving intravenous ketamine for acute asthma exacerbation did not experience significant improvement compared to standard treatment. 28 In spite of the growing interest in the use of ketamine for asthma treatment, conflicting conclusions may be due to the limited sample size, insufficient large-scale prospective studies, and incomplete understanding of the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous recommendations advocated intravenous magnesium sulfate (IVMS) as a safe and effective therapy choice for adult patients with severe acute asthma who did not respond to first-line medications [ 17 , 18 ]. Magnesium sulfate is a physiological blood coagulation mediator that aids in releasing histamine and acetylcholine, resulting in bronchodilation.…”
Section: Reviewmentioning
confidence: 99%
“…Infected patients may need respiratory support based on their disease severity, including supplemental oxygen therapy, continuous positive airway pressure (CPAP), and invasive mechanical ventilation and intubation. Hence, some of these patients who need prolonged intubation might benefit from tracheostomy [3]. Tracheostomy in COVID-19 patients can be performed in cases of prolonged intubation for more than 21 days and in patients with a known difficult airway [4].…”
Section: Introductionmentioning
confidence: 99%